Board Diversity As Antecedent And Corporate Social Responsibility As Consequence Of Earnings Management: Malaysian Evidence - Shafai, Nor Atikah (2019)
Earnings management practices have escalated in recent years. The consequence of this practice is detrimental, and has received immense attention from academician and practitioners. The issue of earnings management has become a serious concern, especially in corporate governance ability as a monitoring mechanism and the consequence of earnings management manifestation. Using Agency Theory and Human Capital Theory, this research endeavours to investigate the relationship between board diversity (diversity-of-boards and diversity-in-boards) and earnings management. This research also determines to examine corporate social responsibility (CSR) as the consequence of earnings management based on Stakeholder-agency Theory and Signalling Theory. Particularly, this study investigates whether earnings management affects the quality of CSR disclosure. Additionally, this research examines the moderating effect of corporate reputation between earnings management and CSR. A total of 265 public listed companies on the Main Market of Bursa Malaysia for the year 2016 have been analysed. This study reveals that board leadership, multiple directorships, gender diversity and age diversity are significantly negative in relation to earnings management. Non-executive directors‘ commitment and nationality diversity, on the other hand, are found to be significant and positively associated with earnings management. The remaining variables which are board size, ethnic diversity and competency diversity were found to have no effect in mitigating earnings management.